PENGARUH MOTIVASI, ETOS KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA SEKWAN DPRD KOTA SUNGAI PENUH - Faisal Amri (Gapenas Publisher, 2022)
This study aims to determine the effect of motivation, work ethic, and work discipline on employee performance at the DPRD Sekwan Sungai Penuh City partially and simultaneously. Respondents of this study were 42 employees at the DPRD Sungai Penuh City. By performing multiple linear regression test, coefficient of determination, F statistical test (simultaneous) and t statistical test (partial). Research results There is a positive and significant influence between motivation on employee performance as evidenced by t count> t table (2,360> 2,05183) and the magnitude of the influence is 17%. There is a positive and significant influence between Work Ethics on employee performance as evidenced by t count> t table (2.732> 2.05183), and the magnitude of the influence is 18.8%. There is a positive and significant influence between work discipline on employee performance as evidenced by t count> t table (2.417> 2.05183), and the magnitude of the influence is 16.4%. Simultaneously there is a positive and significant influence between Motivation, Work Ethic and Work Discipline on the employee performance of the Sekwan DPRD Sungai Penuh City, which can be proven by F count> F table (9.848> 2.96) and the magnitude of the influence is 52.2%. While the remaining 47.8% is explained by other causative factors which were not examined in this study